(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
The puerperium is the period after the birth of the placenta and ends when the uterine devices return to their pre-pregnancy state with a uterine weight of 60 grams or is called Uterine Involution. Disruption of the involution process that is not perfect and can result in bleeding and maternal death is subinvolution. The process of involution can occur quickly or slowly, one of the factors that can affect uterine involution is postpartum exercise. The purpose of this case study is to find out the description of postpartum exercise in post partum mothers. The research method used is descriptive research method using a case study approach. The results of this case study show that there has been a decrease in the height of the uterine fundus in subject I, namely 12 cm from the top of the symphysis to 4.8 cm from the top of the symphysis, subject II also experienced a decrease in the height of the uterine fundus from 10.5 cm from the top of the symphysis to 4, 3 cm from the top of the symphysis after postpartum exercise. The application of postpartum exercise to postpartum mothers can help speed up the process of uterine involution, one of which can be assessed by measuring the fundal height of the postpartum mother .